1996
DOI: 10.1210/jc.81.11.4144
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the human uterine endometrium during the menstrual cycle

Abstract: To investigate apoptotic changes, we studied the cleavage of DNA in the uterine endometrium obtained from regularly cycling women by a quantitative end labeling of DNA gel fractionation and in situ analysis. The ladder pattern characteristic of the apoptotic cleavage of DNA into fragments of low mol wt was identified at three different phases of the cycle, namely the early proliferative, late secretory, and menstrual phases. However, DNA of high mol wt was predominant in the endometrium during the late prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 0 publications
1
49
0
2
Order By: Relevance
“…Apoptosis is markedly activated in the late secretory phase and decreases in the proliferative early secretory phase of the menstrual period in normal endometrial tissues. In contrast, apoptotic activity decreases in refluxed endometrial tissues during the late luteal and early proliferative phases of menstruation (15). In the present study, we observed the same result as others have described.…”
Section: Park Endometriosis Shows Increased Proliferation Activity supporting
confidence: 93%
“…Apoptosis is markedly activated in the late secretory phase and decreases in the proliferative early secretory phase of the menstrual period in normal endometrial tissues. In contrast, apoptotic activity decreases in refluxed endometrial tissues during the late luteal and early proliferative phases of menstruation (15). In the present study, we observed the same result as others have described.…”
Section: Park Endometriosis Shows Increased Proliferation Activity supporting
confidence: 93%
“…The relationships between apoptosis and uterine physiology have been studied in some species [2][3][4][5][6]. A decrease in the height of the surface epithelium coincident with apoptosis from proestrus to midestrus in the rat [6] and strong apoptosis in the human uterus during the late secretory phase of the menstrual cycle [2] have been confirmed by TUNEL assay.…”
Section: Apoptosis In the Porcine Endometriummentioning
confidence: 89%
“…Dynamic changes in the uterine endometrium are a type of homeostasis and proceed with proliferation and exclusion of cells. Homeostasis of the uterus is closely related to apoptosis and involves various hormones and cytokines [1][2][3][4][5][6]. Structural changes in the human endometrium during the menstrual cycle have been studied from the viewpoint of apoptosis [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of estrogen on the dynamics of activation and nuclear localization of AKT are again well described by the endometrial model system and reveal a strong inverse correlation between the presence of PTEN and active AKT in the nuclear compartment. The levels of active nuclear AKT in the glandular epithelium are low in the early proliferative phase, when the amount of nuclear PTEN is very high and selected cell populations undergo apoptosis (Kokawa et al, 1996) and then increase to peak in the late proliferative phase, when nuclear PTEN starts declining and proliferation is at its peak (Guzeloglu-Kayisli et al, 2003). In the secretory phase, when cells do not proliferate and prepare for apoptosis, nuclear AKT levels are very low, as are those of PTEN.…”
Section: Pi3k Signaling In the Nucleusmentioning
confidence: 99%